Design and Application of Bidirectional Converter Based on DAB for Hydrogen Energy Dual-source Locomotive - LUO Pan; RAO Peinan; ZHOU Fengwu; ZHANG Xiaoyong; ZHOU Shuai; ZHANG Qing (Kongzhi Yu Xinxi Jishu)
Compared with traditional diesel locomotive and electric locomotive, hydrogen energy dual source locomotive uses hydrogen fuel cell for power supply, which is not only safer and more environmentally friendly, but also has low operating noise, low cost and more convenient maintenance. As a key component of hydrogen energy system, bidirectional DC/DC converter converts fuel cell voltage into working voltage required by the system, but the existing bidirectional DC/DC converter generally adopts non isolated chopper circuit, which has the disadvantages of not realizing online switching of power flow direction, not redundant operation, etc., thus limiting its application in hydrogen energy dual source locomotive. Therefore, this paper designs a bi-directional isolated DC/DC converter, which uses dual active bridge (DAB) circuit, has wide soft switching range, high conversion efficiency, and can realize bidirectional flow of energy and online switching of transmission direction, with electrical isolation and thermal redundancy functions. This paper describes the main circuit design and control strategy of a 440 kW bi-directional isolated DC/DC converter, innovatively proposes a design method of energy storage inductor, which takes the minimum of the peak current of inductor as the optimization objective.The feasibility of the design is verified through principle simulation and test. The converter efficiency can reach 96%, which successfully realizes the loading application of high-power bi-directional isolated converter in hydrogen locomotive.